Effects of high-speed spin on the reacting flow of drag reduction equipment under rapid depressurization. (25th February 2022) - Zhou, Shupei; Yu, Yonggang
Highlights: The coupled combustion of two gases under dual environmental stress was simulated. The effects of spin on the reaction flow under depressurization were analyzed. A vortex core forms with a high tangential velocity gradient in the spin case. Mass addition is a primary factor for the spin to improve the device performance. Abstract: The drag reduction equipment (DRE) suffers dual environmental stress of high-speed spin and rapid depressurization during the launching process, disturbing the projectile intensely. To research the effect of this extreme process on heat and mass transfer, flow field development, as well as drag reduction performance of the DRE, a numerical model was established based on the MT-based pyrotechnics combustion mechanism and the H2 -CO combustion mechanism. Simulation on the unsteady reacting flow was conducted to investigate the effect of high-speed spin on the performance of the DRE under depressurization. The results indicate that the wake flow field of the DRE transforms from a supersonic under-expanded jet into a subsonic swirling flow, and two recirculation zones with low-pressure appear at the base of the DRE. The transition region between propellant gas and igniter gas in the combustion chamber displays the Kelvin-Helmholtz instability, in which a vortex core forms with a high tangential velocity gradient. The igniter gas burns in the combustion chamber, resulting in an axial high-temperature region. And then the combustion products of igniter gas are mixed with propellant gas and inject outwards, reacting with the air near the jet boundary to be an intense post-combustion. High-speed spin improves the nozzle mass flow rate, enhancing the post-combustion. Eventually, compared with the non-spin case, the mass flow rate and base temperature in the case of 20, 000 rpm are improved by 67.6% and 21.56%, respectively. And the base drag is reduced by 10.14%.